Cooperative interference power allocation in physical layer security under imperfect time synchronization - Wenbo GUO; Changqing SONG; Rong WEN; Hongzhi ZHAO; Youx TANG (Tongxin xuebao)
In physical layer security,considering imperfect time synchronization,a power allocation scheme was proposed to maximize the system secrecy capacity.By analyzing the residual interference power at the authorized receiver caused by imperfect time synchronization,the optimal power distribution method was given,and the relationship between the optimal interference power and the relative channel quality was discussed.Theory and simulation analysis show that when the synchronization error is small,the synchronization error consumes extra power to reach the preset secrecy capacity,and the interference power increases with its increase.As the synchronization error increases,the secrecy capacity of the system gradually fails to reach the preset target,and may even drop to zero.